2007
DOI: 10.1007/s10832-007-9341-x
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of MgO-coated TiO2 nanotubes and application to dye-sensitized solar cells

Abstract: Dye-sensitized solar cells (DSCs) are more spotlighted than conventional photovoltaic devices due to their relatively low cost, easy fabrication and high efficiency. However, there are limitations to increase the conversion efficiency of DSCs. The limiting factors are the quantity of dye adsorption and charge recombination between TiO 2 electrode and electrolyte. Coating other materials such as high energy band gap insulators or semiconductors on the TiO 2 electrode enhances dye adsorption and reduces charge r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Increased photocurrents by PC 61 BM interlayer overcame V oc offset to negative potential and improved the power conversion efficiency of DSCs. It has been reported that blocking back-transfer of photoelectrons not only reduces charge recombination between TiO 2 films and liquid electrolyte but also improves V oc [8,19]. However, V oc was decreased by PC 61 BM interlayer despite of its blocking effect.…”
Section: Inorganic Surface Passivation Of Tio 2 Nanotube Arrays For Dscsmentioning
confidence: 98%
See 4 more Smart Citations
“…Increased photocurrents by PC 61 BM interlayer overcame V oc offset to negative potential and improved the power conversion efficiency of DSCs. It has been reported that blocking back-transfer of photoelectrons not only reduces charge recombination between TiO 2 films and liquid electrolyte but also improves V oc [8,19]. However, V oc was decreased by PC 61 BM interlayer despite of its blocking effect.…”
Section: Inorganic Surface Passivation Of Tio 2 Nanotube Arrays For Dscsmentioning
confidence: 98%
“…Firstly, surface-passivating layer reduces charge recombination between TiO 2 films and liquid electrolyte [5,8,15,19]. Electrons in TiO 2 films usually resides at surface trap states [30].…”
Section: Effects Of Surface Passivation Of Photoelectrodes In Dscsmentioning
confidence: 99%
See 3 more Smart Citations